Therapeutic effect of Nivolumab for advanced / recurrent temporal bone squamous cell carcinoma. Issue 5 (October 2020) - Noda, Teppei; Komune, Noritaka; Yasumatsu, Ryuji; Tsuchihashi, Nana Akagi; Tamae, Akihiro; Matsumoto, Nozomu; Sato, Kuniaki; Uchi, Ryutaro; Koike, Kensuke; Wakasaki, Takahiro; Tanaka, Risa; Nakagawa, Takashi
Abstract: Objective: The immune checkpoint inhibitor Nivolumab was approved for the treatment of platinum-refractory head and neck squamous cell carcinoma (SCC), expanding the treatment options for recurrent or advanced head and neck SCC. However, since temporal bone squamous cell carcinoma (TB-SCC) is very rare cancer, the effectiveness of Nivolumab remains unclear. We investigated the effects of Nivolumab for TB-SCC. Method: Chart information was collected for all patients who underwent the first administration of Nivolumab for recurrent or residual TB-SCC in our hospital between September 2017 and December 2019. Tumor staging followed the modified Pittsburgh classification. Changes in the tumor burden and survival outcome were examined. Results: We examined 9 patients with recurrent or residual TB-SCC who started administration of Nivolumab. In these cases, recurrent or residual SCC was observed after chemotherapy and/or chemoradiotherapy including platinum. The duration of Nivolumab was 2–54 weeks (median 20.0 weeks). The evaluation of the therapeutic effect according to the RECIST method showed partial response in 1 case, stable disease in 2 cases, progressive disease in 4 cases, and size unevaluated in 2 case. Although the number of cases was small, comparing with 5 cases without Nivolumab, these cases showed longer overall survival (1-year OS 33.3% vs 20.0%). Conclusion: We used Nivolumab as palliative chemotherapy in 9 patients with recurrent/residual TB-SCC, and we were able to obtain a certain therapeutic effect on TB-SCC as well as other head and neck SCC.